Measuring Bali State Polytechnic International Competitiveness through Balanced Scorecard Approach - I Putu Mertha Astawa; Luh Mei Wahyuni (Politeknik Negeri Bali, 2019)
This study aims to measure the achievement of the international competitiveness of Bali State Polytechnic (BSP) by utilizing four Balanced Scorecard (BSC) perspectives, namely: learning & growth, internal business process, customer, and financial. This study uses a qualitative approach that analyzes the performance of international competitiveness. Data was collected through observation techniques, questionnaires, and documentation. The study sample consisted of 135 people using the judgmental sampling technique and random sampling technique. Research respondents were Institutional Leaders, Head of Units, Head of Departments, Head of Study Programs, and Section Heads were 35 respondents and students were 100 respondents. The results of the study show that the performance of BSP in ​​building international competitiveness in the customer's perspective and financial perspective is still not good. As for the internal business perspective, and the perspective of growth and learning is bad. Poor performance has resulted the international competitiveness performance not achieving the target as stated in the strategic plan.